Theoretical and methodical knowledge of students of discipline "Physical education" - Berezka S.M (Kharkov National Pedagogical University, 2011)
Article is devoted to optimization problem of theoretical and methodical students knowledge's within the pale of sparring discipline "Physical education". Author offers to posit valeological approach in acquirement of knowledge's from discipline, accepting this as one of motivation rise methods to employments by physical education and propaganda's of healthy mode of life. It is proved that students at the age of 17-25 years old have specific anatomic physiological characteristics, so physical education must favour students' organism forming.